A look at indirect tax system in Turkey based on demand system estimation - Soydan, Gürcan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
Taxation systems are not established only to raise the necessary revenue for the government budget. A redistributive function is also generally attributed to those systems to alleviate income inequality problems. A properly designed and efficiently exercised direct taxation system can help to solve an important part of inequality by directly taxing individuals and corporates according to their earnings. However, developing countries, including Turkey, for several reasons, usually rely on indirect taxes rather than direct income taxes for the collection of the government revenue. The purpose of this study is to analyse the indirect taxation system in Turkey on distributional grounds. Marginal Tax Reform Analysis is applied for the indirect tax system in effect in 2003. 2003 Household Budget Survey of the Turkish Statistical Institute (TurkStat) is used in exploring the consumption pattern of the households in Turkey and obtaining the necessary price elasticities. The indirect taxes in 2003 are found not to be optimal. At different levels of inequality aversion for the government, the same amount of revenue can be raised by adjusting the indirect tax rates.
Keywords: Indirect taxation -- Turkey.; Taxation -- Turkey.